HE EFFECT OF PROTEAN CAREER ATTITUDES AND BOUNDARYLESS CAREER ATTITUDES TO CAREER SATISFACTION’S LECTURERS WITH THE ROLE OF CAREER ADAPTABILITY AS A MEDIATOR - Natasya, Asmo Dini; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine what the positive effect of protean career attitudes are and unlimited career attitudes on career satisfaction of permanent lecturers with career adaptation variables as mediators. This research method is quantitative with a population of Semarang State University and Walisongo Islamic State University. The sampling technique uses proportional random sampling and the number of samples is 125 respondents. The data analysis method uses descriptive statistical tests and SmartPLS software version 3.0. The results showed that career adaptability is able to mediate the influence of protean career attitudes and boundaryless career attitudes on career satisfaction. For further research are to expand the object of research in various sectors of the company that have higher career prospects with different cultures and for Semarang State University and Walisongo Islamic State University can provide the widest opportunity for educators to develop their skills and mindset for improvement quality of learning and newness of expertise.